Epigenetics and atherosclerosis - Turunen, Mikko P.; Aavik, Einari; Ylä-Herttuala, Seppo (Biochimica et biophysica acta, 2009)
The contribution of epigenetic mechanisms to cardiovascular diseases remains poorly understood. Hypomethylation of genomic DNA is present in human atherosclerotic lesions and methylation changes also occur at the promoter level of several genes involved in the pathogenesis of atherosclerosis, such as extracellular superoxide dismutase, estrogen receptor-α, endothelial nitric oxide synthase and 15-lipoxygenase. So far, no clear data is available about histone modification marks in atherosclerotic lesions. It remains unclear whether epigenetic changes are causally related to the pathogenetic features, such as clonal proliferation of lesion smooth muscle cells, lipid accumulation and modulation of immune responses in the lesions, or whether they merely represent a consequence of the ongoing pathological process. However, epigenetic changes could at least partly explain poorly understood environmental and dietary effects on atherogenesis and the rapid increases and decreases in the incidence of coronary heart disease observed in various populations. RNAi mechanisms may also contribute to the epigenetic regulation of vascular cells. Therapies directed towards modification of the epigenetic status of vascular cells might provide new tools to control atherosclerosis-related cardiovascular diseases.